BRAF mutation in fine‐needle aspiration specimens as a potential predictor for persistence/recurrence in patients with classical papillary thyroid carcinoma larger than 10 mm at a BRAF mutation prevalent area. Issue 10 (9th February 2015) - Moon, Hee Jung; Kim, Eun‐Kyung; Chung, Woong Youn; Shin, Dong Yeob; Kwak, Jin Young
Abstract: Background: The association between the BRAF mutation and persistence/recurrence was investigated in patients with classical papillary thyroid carcinoma (PTC) at a BRAF mutation prevalent area. Methods: A total of 282 patients with total thyroidectomy and prophylactic central neck dissection were included in this study. The BRAF mutation was evaluated with cytology specimen using dual priming oligonucleotide (DPO)‐based multiplex polymerase chain reaction (PCR) and direct sequencing preoperatively. Results: Thirty‐four patients (12%) had persistence/recurrence. In all PTC, the BRAF mutation on both methods was not associated with persistence/recurrence. In PTC >10 mm, the BRAF mutation on DPO‐based multiplex PCR was significantly associated with persistence/recurrence and a potential predictor for persistence/recurrence. In PTC ≤10 mm, none of the covariates were significantly different between patients with and without persistence/recurrence. Conclusion: The BRAF mutation was significantly associated with persistence/recurrence and a potential predictor in patients with classical PTC >10 mm at a BRAF mutation prevalent area. © 2015 Wiley Periodicals, Inc. Head Neck 37: 1432–1438, 2015